Integrated farm management for sustainable agriculture: Lessons for knowledge exchange and policy. (February 2019) - Rose, David C.; Sutherland, William J.; Barnes, Andrew P.; Borthwick, Fiona; Ffoulkes, Charles; Hall, Clare; Moorby, Jon M.; Nicholas-Davies, Phillipa; Twining, Susan; Dicks, Lynn V.
Abstract: As a response to the environmentally and socially destructive practices of post-war mechanization and intensification, the concept of sustainable agriculture has become prominent in research, policy, and practice. Sustainable agriculture aims to balance the economic, environmental, and social aspects of farming, creating a resilient farming system in the long-term. Over the last few decades, various concepts have been used in research and policy to encourage the adoption of sustainable practices. Within such a congested space, this paper assesses the value of 'integrated farm management' as a concept for the promotion of sustainable agriculture. The concept is the subject of renewed policy interest in England and Wales and it is also being promoted in Europe. Previous research, however, has suggested that integrated farm management may not be well understood or widely practised. There are also criticisms that it can be impractical and poorly differentiated from similar ideas. As such, renewed insights are required into how useful the concept might be for encouraging sustainable agriculture. Using a mixed methods approach, we gathered the views of farmers, farm advisors, and industry representatives about integrated farm management in England and Wales, and interpreted these through a theoretical framework to judge the strength of the concept. Overall, the general principles of Integrated Farm Management were found to be coherent and familiar to most of our respondents. However, the concept performed poorly in terms of its resonance, simplicity of message, differentiation from other similar terms and theoretical utility. We reflect on our findings in the context of other ways to promote sustainable agriculture, drawing out messages for policy and knowledge exchange in England and Wales, as well as elsewhere.